Emerging technologies for non-invasive quantification of physiological oxygen transport in plants - Chaturvedi, P.; Taguchi, M.; Burns, S. L; Hauser, B. A; Wan Salim, Wan Wardatul Amani; Clausen, J. C.; McLamore, E. S (Springer Berlin Heidelberg, 2013)
Oxygen plays a critical role in plant metabolism, stress response/signaling, and adaptation to environmental changes (Lambers and Colmer, Plant Soil 274:7–15, 2005; Pitzschke et al., Antioxid Redox Signal 8:1757–1764, 2006; Van Breusegem et al., Plant Sci 161:405–414, 2001). Reactive oxygen species (ROS), byproducts of various metabolic pathways in which oxygen is a key molecule, are produced during adaptation responses to environmental stress. While much is known about plant adaptation to stress (e.g., detoxifying enzymes, antioxidant production), the link between ROS metabolism, O2 transport, and stress response mechanisms is unknown. Thus, non-invasive technologies for measuring O2 are critical for understanding the link between physiological O2 transport and ROS signaling. New non-invasive technologies allow real-time measurement of O2 at the single cell and even organelle levels. This review briefly summarizes currently available (i.e., mainstream) technologies for measuring O2 and then introduces emerging technologies for measuring O2. Advanced techniques that provide the ability to noninvasively (i.e., non-destructively) measure O2 are highlighted. In the near future, these non-invasive sensors will facilitate novel experimentation that will allow plant physiologists to ask new hypothesis-driven research questions aimed at improving our understanding of physiological O2 transport